Arcanumophis, a new genus and generic allocation for Erythrolamprus problematicus (Myers 1986), Xenodontinae (Colubridae) from the Cordillera de Carabaya, southern Peru - Smaga, Christopher R.; Ttito, Alex; Catenazzi, Alessandro (Zootaxa, 2019)
The systematics of South American Xenodontinae snakes has experienced large changes and improvements as a result of recent studies employing molecular data. Herein we assess the status of the rare Peruvian snake species, Erythrolamprus problematicus (Dipsadidae, Xenodontinae, Xenodontini), previously known from a single specimen collected in 1950. Based on new morphological and molecular data from a second specimen that we collected, we confirmed the presence of a crease in the rostral scale, mentioned in the original description (a unique trait among the Xenodontini), and recovered E. problematicus as the sister-taxon of all other Xenodontini, instead of nested among the current Erythrolamprus. Therefore, our phylogenetic results justify the erection of a new genus to accommodate the species.